Pendampingan Manajemen SDM untuk Optimalisasi Kinerja Guru dan Staf Sekolah - Moh Usman Kurniawan; Neviyani Neviyani; Noviana Mariatul Ulfa; Denok Mugi Hidayanti (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The community service activity titled